The impact of intangible capital on the productivity of small firms - Kostevc, Črt (Economic and business review, 2022)
Despite the mounting evidence in support of the role of intangible capital on firm performance, some research gaps remain. This paper focuses on the link between intangible capital and firm performance with a particular focus on the effect firm size has on the relationship by studying the population of Slovene enterprises between 2007 and 2020. We find that while intangible assets are positively associated with productivity, the link is by no means linear. Furthermore, micro firms appear to benefit most from investing in intangible assets, while the effect is less robust for small and medium-size enterprises (SMEs) and large firms. Amongst different types of intangible assets, the strongest effect on productivity was found for investment in property rights and goodwill, while long-term deferred development costs had a weaker effect on firm productivity.
Keywords: intangible assets; majhna podjetja; nematerialne naložbe; productivity; produktivnost; small enterprises